The content of photosynthetic pigments in leaves of Berberis thunbergii forms in the Kherson region (CHORNOMORSKI BOTANICAL JOURNAL, 2019)
We carried out comparative studies of the photosynthetic pigments content in leaves of one- and two-year shoots in eight decorative forms of Berberis thunbergii DC. from the Agrobiostation – Botanical Garden collection of the Kherson State University. The chlorophyll content and carotenoids sum were defined in the leaves of these forms in July and early October, when there were no visual signs of leaf aging. The forms are differed by various colours of leaves: green, green with white-gray spots, purple, purple with yellow strip, purple with white-gray spots, yellow. In October, the chlorophyll content and carotenoids was higher than in the leaves of the same forms in July in the vast majority of forms. The maximum levels of the chlorophylls (2.51 mg/g) and carotenoids (0.89 mg/g) were found in green-coloured leaves with white-gray spots in the form “Kelleris” in October. In July, these rates were 2.11 mg/g and 0.64 mg/g respectively. The lowest content of the chlorophylls (0.22 mg/g) and carotenoids (0.11 mg/g) were in July in the leaves of two-year shoots of the yellow-leaf dwarf "Bananza gold". The content of photosynthetic pigments were generally higher in the leaves of one-year shoots vs. two- year ones. Ratio of chlorophyll a/chlorophyll b to chlorophyll sum/ carotenoids sum were varied during the growing season. It is varied from 1.0 to 3.1 and 1.0 to 3.3 in July and from 1.9 to 3.1 and from 1.3 to 4.0 in October. Usually, forms with green leaves had a higher content of the chlorophyll a and b and their sums vs. forms with purple and especially yellow leaves. This applies to the carotenoids sum in July also. In October, most carotenoids were found in leaves of the forms with purple leaf color, exception for the form “Kelleris”. The significant differences in the leaf colouring of decorative forms B. thunbergii are a real guarantee for the creation of colourful garden arrangements in parks and squares.
Keywords: Berberis, botanical garden, chlorophyll, carotenoids, Ukraine.